Antimicrobial Susceptibility Profile of Salmonella enterica Serovars and Determination of Minimum Inhibitory Concentration of Ciprofloxacin and Cefotaxime - Subedi, Kusum; Gautam, Sushma; Swar, Rajeshwori; Arjyal, Charu; Rijal, Basista Prasad (Tribhuvan University Journal of Microbiology, 2024)
Objectives: To study the antibiotic susceptibility profile of Salmonella enterica serovar Typhi and Paratyphi A and determine the minimum inhibitory concentration of Cefotaxime and Ciprofloxacin. Methods: Blood samples from patients suspected of enteric fever were cultured following standard microbiological techniques. Antibiotic susceptibility tests for commonly used drugs were performed by modified Kirby Bauer disc diffusion technique following the guidelines of Clinical and Laboratory Standard Institute (CLSI). Determination of minimum inhibitory concentration (MIC) was done by agar dilution method. Results: A total of 1,328 blood samples were processed out of which 64 were culture positive. Among the 33 isolates of Salmonella enterica, 22 were Salmonella Typhi while the rest 11 were Salmonella Paratyphi A. This study showed that 96.96% of isolates were resistant to Nalidixic acid and 87.87% were resistant to Ciprofloxacin. In contrast, 93.93% isolates were sensitive to Ampicillin and 90.90% were sensitive to Cefixime. 65.62% isolates were resistant with MIC ≥1 µg/ml against Ciprofloxacin while against Cefotaxime, 53.12% isolates were sensitive with MIC ≤1 µg/ml. Conclusion: Fluoroquinolones have shown the reduced susceptibility towards Salmonella Typhi and Salmonella Paratyphi A making them inappropriate to use for treating enteric fever. Ampicillin and Cefixime were found to be highly susceptible suggesting them for possible treatment. However, susceptibility testing must be done before the administration of any antibiotics.